Increased levels of IL-4 in the Spleen of BALB/c Mice after 65.5 kDa Pili Protein Klebsiella pneumoniae Immunization - Putra Uta, Diego Rafi; Mufida, Diana Chusna; Sutejo, Ika Rahmawati; Agustina, Dini; Suswati, Enny; Shodikin, Muhammad Ali (Medical Laboratory Technology Journal, 2024)
Pneumonia is an infection of the lung parenchyma caused by Klebsiella pneumoniae, resulting in a high mortality rate of millions each year. To reduce these deaths, one potential solution is to create a vaccine that utilizes virulence factors of this microorganism, such as pili. During the early phase of infection, these antigens have a crucial role and can stimulate the production of memory b cells. These cells are activated by IL-4 (interleukin-4) in lymphoid organs, such as the spleen. Pathogen exposure such as virulence factors can stimulate the secretion of IL-4 in the spleen organ. This study aims to investigate the role of Klebsiella pneumoniae pili in this process. The research conducted from May to December 2023 at the Microbiology Laboratory, Faculty of Medicine, University of Jember was purely experimental, using Balb/c mice with IL-4 levels in the spleen organ as variables. The study used 15 mice, divided into control (K1), adjuvant (K2), and antigen (K3) groups. The research data were analyzed using non-parametric tests, specifically the Kruskal-Wallis and Post Hoc tests. The Kruskal-Wallis test revealed significant differences (p=0.003). In the Post Hoc test, a significant difference was found between the control and antigen groups (p=0.002). The results conclusively demonstrate that induction of Klebsiella pneumoniae pili protein 65.5 kDa significantly increases IL-4 levels in the spleen. Future studies should consider adding serum specimens to provide additional information.